Effect of different land use and land use change on ammonia oxidiser abundance and N2O emissions. (May 2016) - Li, Chaoyu; Di, Hong J.; Cameron, Keith C.; Podolyan, Andriy; Zhu, Baocheng
Abstract: In recent years, there has been a major expansion of dairy farming in New Zealand, largely as a result of land use change from forestry and sheep farming to dairy farming. Possible impacts of different land uses and land use change on ammonia oxidising bacteria (AOB) and archaea (AOA) and N2 O emissions are not well understood. A field study was carried out to determine the effects on AOB and AOA abundance by three long-term different land uses, pine tree plantation (30+ years), sheep farming (30+ years) and dairy farming (12+ years), located in close proximity on the same soil type. A laboratory incubation study was carried out to determine the impact of dairy cow urine application (simulating the deposition of dairy cattle urine after the conversion of tree plantation and sheep farming to dairy farming) on AOB and AOA growth and N2 O emissions. The results showed that AOB abundance was higher in the dairy and sheep farm soils ( P  < 0.05) than in the pine tree soil but that the AOA abundance was higher in the sheep farm soil than in the dairy and pine tree soils ( P  < 0.05). When dairy cow urine was applied in the incubation study, the AOB growth was initially faster in the dairy, followed by sheep and then followed by the pine tree soil, but the growth continued for an extended period in the pine tree soil with the amoA gene copy numbers eventually exceeding those in the sheep and dairy pasture soils. AOA grew following urine application in the sheep soil but did not change in the other soils. Total N2 O emissions in the pine tree soil was more than twice those from the dairy and sheep farm soils. These results demonstrate the significant impact of land use and land use change on ammonia oxidiser communities and subsequent impacts on nitrogen transformations and N2 O emissions. Further research is needed to verify these results in the field. Highlights: Land use type and change had a major impact on ammonia oxidising bacteria (AOB) and archaea (AOA). AOB abundance was higher in dairy and sheep farm soils than in a pine plantation soil. AOA was higher in the sheep farm soil than in the dairy and pine plantation soils. Unexpectedly, AOA in the sheep farm soil grew in response to dairy cow urine application. N2 O emissions from the pine tree soil were the highest following urine application.